Politics, Protest and Young People Political Participation and Dissent in 21st Century Britain - Pickard, Sarah (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
Sarah Pickard offers a detailed and wide-ranging assessment of electoral and non-electoral political participation of young people in contemporary Britain, drawing on perspectives and insights from youth studies, political science and political sociology. This comprehensive book enquires into the approaches used by the social sciences to understand young people's politics and documents youth-led evolutions in political behaviour. After unpicking key concepts including 'political participation,' 'generations,' the 'political life-cycle,' and the 'youth vote,' Pickard draws on a combination of quantitative and qualitative research to trace the dynamics operating in electoral political participation since the 1960s. This includes the relationship between political parties, politicians and young people, youth and student wings of political parties, electoral behaviour and the lowering of the voting age to 16. Pickard goes on to discuss personalised engagement through what she calls young people's (DIO) Do-It-Ourselves political participation in online and offline connected collectives. The book then explores young people's political dissent as part of a global youth-led wave of protest. This holistic book will appeal to anyone with an interest in young people, politics, protest and political change.